Meta-analysis of gut microbiome studies identifies disease-specific and shared responses - Claire Duvallet (Nature Portfolio, 2017)
Reported associations between the human microbiome and disease are often inconsistent. Here, Duvallet et al. perform a meta-analysis of 28 gut microbiome studies spanning ten diseases, and find associations that are likely not disease-specific but potentially part of a shared response to disease.